Hirayama Disease – A case report - Sharma, Bharat B; Sharma, Shashi; Sharma, Sandeep; Oberoi, Nitin; KSV, Abhinetri (Indian Journal of Child Health, 2014)
Hirayama Disease is a non-progressive juvenile spinal muscular atrophy of the distal upper limb. The flexionmovement results in cervical myelopathy which affects the dorsal aspect of the cervical cord. It is a benign motor neuron disorder and its initial course is progressive which subsequently becomes stationary. These findings are quite sensitive to magnetic resonance imaging in flexion position which sometimes may be missed in neutral position. We hereby report a case an adolescent boy who presented with asymmetrical weakness of both hands and his magnetic resonance imaging in flexion revealed changes suggestive of Hirayama disease.